2007
DOI: 10.1245/s10434-007-9393-9
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Value of Circulating Tumor Markers in Patients with Pseudomyxoma Peritonei Treated with Cytoreductive Surgery and Hyperthermic Intraperitoneal Chemotherapy

Abstract: Normal CA125 correlated to the likelihood to achieve adequate CRS, which is a significant prognostic factor for PMP. Increased baseline CA19.9 was an independent predictor of worse PFS after CRS and HIPEC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
57
1
5

Year Published

2008
2008
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 91 publications
(67 citation statements)
references
References 24 publications
4
57
1
5
Order By: Relevance
“…We rationalised the following: (i) serum CEA and CA19-9 levels are elevated in over 50% PMP patients at presentation and drop markedly following cytoreductive surgery and HIPEC (van Ruth et al, 2002); (ii) elevated CA 19-9 levels prior to cytoreductive surgery may be an independent predictor of worse progression-free survival (Baratti et al, 2007); and (iii) in a case study of a patient with DPAM treated with capecitabine, there was a decrease in CEA and CA19-9 levels (Levitz et al, 2004). Serum CA125 concentrations are commonly raised in patients with PMP, and at initial presentation, may mimic gynaecological malignancies (Pranesh et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…We rationalised the following: (i) serum CEA and CA19-9 levels are elevated in over 50% PMP patients at presentation and drop markedly following cytoreductive surgery and HIPEC (van Ruth et al, 2002); (ii) elevated CA 19-9 levels prior to cytoreductive surgery may be an independent predictor of worse progression-free survival (Baratti et al, 2007); and (iii) in a case study of a patient with DPAM treated with capecitabine, there was a decrease in CEA and CA19-9 levels (Levitz et al, 2004). Serum CA125 concentrations are commonly raised in patients with PMP, and at initial presentation, may mimic gynaecological malignancies (Pranesh et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…It has been clearly demonstrated that a combined approach of CRS and HIPEC is the standard treatment of patients with PPM because it is able to provide a survival advantage compared with historical controls. Treatment failure may be predicted by several prognostic factors, which were validated in large series [6,[16][17][18]. Several retrospective analyses documented that previous use of systemic chemotherapy was an independent poor prognostic factor for patients undergoing curative CRS and HIPEC for appendiceal neoplasms associated with PPM [19][20][21].…”
Section: Discussionmentioning
confidence: 99%
“…However, the role of serum tumour markers has been underlined. In patients with peritoneal mesothelioma, we reported a sensitivity rate of 100% (12/12) for CA125 in assessing disease progression after complete CRS and HIPEC [46] In patients with pseudomyxoma peritonei with positive baseline values, marker concentrations at progression were elevated in 24 of 29 (82.7%) patients for CEA, in 18 of 22 (81.8%) patients for CA19.9, in 12 of 19 (63.1%) patients for CA125, and in 4 of 6 (66.7%) patients for CA15.3 [47] . Van Ruth reported that CEA normalized in 73% patients and CA19.9 in 57% patients with preoperative increased levels, and that CA19.9 was positive in 14 of 14 cases of relapsing PMP with elevated preoperative levels [48] .…”
Section: Long Term Follow-upmentioning
confidence: 99%